Action Research Workshop Series Plan to Support Uptake of ICT and Interactive Pedagogy in Maharashtra Schools - Tara Stafford Ocansey; Anchal Sharma (Columbia University, Earth Institute, Center for Sustainable Development (CSD), 2019)
Maharashtra State has identified the use of technology in teaching as a key area for helping to facilitate rapid improvement in learning outcomes for students across the state. Ready to invest further in this area, the state is interested in identifying the most effective tools and approaches for various types of learning environments within the state that can be scaled up. The research team from the Center for Sustainable Development and The Energy and Resource Institute launched a research initiative in Maharashtra to study efforts made in the area of ICT for improved education quality in December 2018. The research focus initially looked specifically at the rollout of DIKSHA (Digital Infrastructure for Knowledge Sharing platform), but is expanding the scope to look more holistically at how support and training for teachers and content creators can help facilitate development and use of more locally relevant content both on the DIKSHA platform and beyond for teachers across Maharashtra. Based on the feedback from education stakeholders in Maharashtra, the research team identified a range of areas where further action research and training support could help contribute to increased uptake of ICT in education and with higher rates of satisfaction with the DIKSHA platform more specifically. These areas include: 1. Training on quality standards 2. Pedagogical training for integrating ICT and interactive pedagogy 3. Formalized feedback mechanism within the platform 4. Formalized content submission and review process 5. Disaggregated usage data. (...)
Keywords: 330